(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Prenatal diagnosis of congenital anomalies and hereditary human diseases is a new direction in clinical and medical genetics. The purpose of prenatal diagnosis is the diagnosis, prevention and intrauterine treatment of human hereditary diseases and congenital anomalies. Modern prenatal diagnostics has a complex of human genetic methods that make it possible to detect congenital pathology in the fetus at any stage of pregnancy.